Cancer incidence and spectrum among children with genetically confirmed Beckwith-Wiedemann spectrum in Germany: a retrospective cohort study - Cöktü, Sümeyye; Spix, Claudia; Kaiser, Melanie; Beygo, Jasmin; Kleinle, Stephanie; Bachmann, Nadine; Kohlschmidt, Nicolai; Prawitt, Dirk; Beckmann, Alf; Klaes, Ruediger; Nevinny-Stickel-Hinzpeter, Claudia; Döhnert, Steffi; et al. (British Journal of Cancer, 2020)
Background: Beckwith-Wiedemann syndrome (BWS) is a cancer predisposition syndrome caused by defects on chromosome 11p15.5. The quantitative cancer risks in BWS patients depend on the underlying (epi)genotype but have not yet been assessed in a population-based manner. Methods: We identified a group of 321 individuals with a molecularly confirmed diagnosis of BWS and analysed the cancer incidence up to age 15 years and cancer spectrum by matching their data with the German Childhood Cancer Registry. Results: We observed 13 cases of cancer in the entire BWS cohort vs 0.4 expected. This corresponds to a 33-fold increased risk (standardised incidence ratio (SIR) = 32.6; 95% confidence interval = 17.3-55.7). The specific cancers included hepatoblastoma (n = 6); nephroblastoma (n = 4); astrocytoma (n = 1); neuroblastoma (n = 1) and adrenocortical carcinoma (n = 1). The cancer SIR was highest in patients with a paternal uniparental disomy of 11p15.5 (UPDpat). A high cancer risk remained when cases of cancer diagnosed prior to the BWS diagnosis were excluded. Conclusions: This study confirms an increased cancer risk in children with BWS. Our findings suggest that the highest cancer risk is associated with UPDpat. We were unable to confirm an excessive cancer risk in patients with IC1 gain of methylation (IC1-GOM) and this finding requires further investigation.
CRIS-Team Scopus Importer:2020-06-02